Psychoacoustic performance in children completing Fast ForWord training. - Thibodeau LM; Friel-Patti S; Britt L (American Journal of Speech-Language Pathology, 2001)
It has been hypothesized that one cause of children's language disorders is poor temporal processing. When children are not able to follow the rapid modulations in the speech signal that cue phonemic information, development of critical language concepts might be missed. It has also been suggested that intensive auditory training on a hierarchy of temporal tasks may significantly improve language processing. Temporal processing was evaluated in children with normal language and those with language impairment who were enrolled in an intensive computerized auditory training program. The psychoacoustic tasks were aimed at evaluating the ability to (1) process signals arriving in very close succession, and (2) discriminate signals changing rapidly in frequency. Three dependent variables included thresholds for brief tones presented in three conditions, quiet, just before a masker, and simultaneously with a masker. A fourth dependent variable was the minimum detectable change in a tone sweeping up in frequency. Despite minimal changes in performance over the five-week period, there were overlaps in performance on all tasks between the groups suggesting a complex relationship between temporal processing and language development. Children with language impairment who had better performance on the masking and frequency discrimination tasks showed greater success on the auditory training program.